СВС–твердосплавные материалы инструментального назначения - Левашов, Е.А.; Панов, В.С.; Кудряшов, А.Е.; Погожев, Ю.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
Hard alloys based on titanium-chromium carbide (TiC–Cr₃C₂–Ni) were produced by hightemperature self-propagating synthesis method and sintered hard alloy ВА8 (WC–Ni₃Al) was produced by powder metallurgy technique. Application availability of hard alloy ВА8 as a material for production cutting tools and SHS-materials as electrodes for strengthening of cutting tools, die blocks and forming rolls using Electro Spark Alloying (Deposition) technology was demonstrated.